A retrospective comparison of the mortality of critically ill patients receiving prolonged and standard infusion of meropenem / Noorizan Abd Aziz … [et al.] - Abd Aziz, Noorizan; Hassan, Fahmi; Hassan, Yahaya; Abu Hassan, Haslina (Research Innovation Business Unit, 2014)
Sepsis is defined as infection with systemic manifestations of the infection. Severe sepsis is defined as sepsis plus sepsis-induced organ dysfunction or tissue hypoperfusion. Severe sepsis and septic shock (severe sepsis with hypotension not resolved with fluid resuscitation) are serious medical condition that causes death in 25% of the cases. Half a century back, the mortality rate of sepsis and septic shock were as high as 50% to 75%. Meropenem is a beta-lactam antibiotic, it exhibits the bactericidal effect with time-dependent activity. Theoretically, the longer the infusion time, the longer the concentration of meropenem will remain above a pathogen minimum inhibitory concentration (MIC), thus increasing the efficacy of the drug. The critically ill patients and the normal ward patients will have different pharmacokinetics parameters. Problem Statement: The optimal mode of administration of beta lactam antibiotics in the treatment of bacterial infections remains controversial. Meropenem demonstrates time dependent killing activity. Animal models have shown that concentrations of meropenem should remain above the MIC for approximately 20% or 40% of the dosing interval for the drug to have a bacteriostatic or bactericidal effect, respectively. Research question: Does extending meropenem infusion from 30 minutes to three hours in treating severe infections in critically ill septic patients provide better survival outcomes for the patients? Benefit of the Study: These findings of this study would help decision makers in critical care setting especially clinicians and pharmacists in choosing the best practice to administer meropenem to the patients. Safety and efficacy of both administration strategies could be compared and new protocol of administering meropenem could be developed and used in critical care setting. Objective: To compare the mortality between critically ill patients who received prolonged with standard infusion of meropenem. Methods: A retrospective cohort and cross-sectional study was conducted among patients over 18 years old who were diagnosed with sepsis and received meropenem infusion in Intensive Care Unit (ICU) of three different hospitals in Malaysia. List of ICU patients receiving meropenem will be retrieved from the pharmacy computerized dispensing system records. Patients received either 30 minutes infusion of meropenem or three hour infusion of meropenem as per practice of individual settings. Outcomes and clinical data were collected from the electronic databases and also patients file from the record departments of individual settings. Results: During the study period, a total of 1975 patients received meropenem infusion during their admission in the ICUs. 11.4% of the patients met the inclusion criteria of the study and were included in the analysis. From the 225 subjects, 108 received three-hour infusion of meropenem while the remaining 117 received 30-minute infusion of meropenem. Patients receiving the extended infusion of meropenem were found to have lower mortality rate compared to those receiving the standard infusion of meroepenem (64.1% vs 49.1%, p=0.16). Regression analysis of the data showed that infusion time and age significantly confounded the mortality outcome of the studied patients. Conclusion: Prolonged infusion of meropenem seems to have equal efficacy if not superior to the standard infusion of meropenem.